Association between glycation biomarkers, hyperglycemia, and micronucleus frequency: A meta -analysis - Deo, Permal; Fenech, Michael; Dhillon, Varinderpal S. (Mutation research. Reviews in mutation research, 2021)
Micronucleus assay has been used as a biomarker of DNA damage, chromosomal instability, cancer risk and accelerated aging. In this review, a meta-analysis was performed to assess the association between micronuclei (MNi) and diseases with increased advanced glycation end products (AGEs) and HbA1c. The review identified eight studies with 632 subjects with disease and 547 controls. The Mean Ratio (MRi) for AGE levels (MRi = 2.92, 95 %CI: 2.06–4.13, P < 0.00001) and HbA1c levels (MRi = 1.32, 95 %CI: 1.12–1.56, P = 0.001) were significantly higher in the disease group compared to healthy controls. The meta-analysis indicated that the overall estimates of MRi for MNi was 1.83 (95 %CI: 1.38–2.42, p < 0.0001) in subjects with disease compared to controls. Significant increases in MRi for MNi were also observed in the following sub-groups: subjects with disease for elevated AGEs (MRi = 1.62, 95 %CI: 1.12–2.35, P = 0.01), elevated HbA1c (MRi = 2.13, 95 %CI: 1.33–3.39, P = 0.002), lymphocytes MNi (MRi = 1.74, 95 %CI: 1.29–2.33, P = 0.0003), exfoliated buccal cells MNi (MRi = 2.86, 95 %CI: 1.19–6.87, P = 0.02), type 2 diabetes mellitus (T2DM) (MRi = 1.99, 95 %CI: 1.17–3.39, P = 0.01), chronic renal disease (MRi = 1.68, 95 %CI: 1.18–2.38, P = 0.004) and other disease groups (MRi = 2.52, 95 %CI: 1.28–4.96, P = 0.008). The results of this review suggest that MNi could be used as a biomarker of DNA damage and chromosomal instability in degenerative disease where increased AGEs and HbA1c are implicated. The lack of heterogeneity for MN frequency when considered either for all studies or subgroup strengthened the MRi of the meta-analysis. However, the lack of significant association between MRi for MNi and MRi for AGEs or HbA1c indicates that the case-control studies investigated may be confounded by other variables. Thus, larger studies with long term AGE exposure is warranted to further understand the role of MN formation in the initiation and progression of diseases caused by excessive glycation.